Validity and reliability of the Indonesian version of the Scale for the Assessment of Negative Symptoms - Amin, Mustafa M.; Effendy, Elmeida; Camellia, Vita; Saragih, Munawir; Kamil, Ahmad; Harsono, Rusly (Frontiers in Psychiatry, 2023)
Background Negative symptoms have long been conceptualized as a core aspect of schizophrenia. Despite widespread recognition of the status of these symptoms as independent dimensions of schizophrenia, they are sometimes difficult to distinguish from depression or cognitive impairment. Therefore, objective assessment of schizophrenia symptoms is critical by obtaining a valid and reliable Indonesian version of the SANS instrument. This study aimed to determine the content validity, concurrent, internal consistency reliability, inter-rater, cut-off value, sensitivity, and specificity of the SANS instrument. Methods This is a diagnostic study using the cross-sectional method to determine the relationship between the SANS and PANSS instruments on the negative symptom subscale. It was located at the Prof. Dr. M. Ildrem Mental Hospital of North Sumatera Province. Results Of the 400 subjects, 67.5% were males, and the median age of the subjects was 37 years (18–45). The results of the content validity test were good (mean I-CVI=1.00), and the concurrent validity test comparing the SANS and PANSS instruments on the negative symptom subscale obtained significant results (p < 0.001) with a strong correlation (r = 0.763). Additionally, the consistency reliability test had a very high internal score (Cronbach alpha = 0.969), the overall inter-rater reliability test was “very good” (ICC = 0.985), and the cut-off value was 10.5 with sensitivity and specificity values of 72.9 and 77.9%, respectively. Conclusion The Indonesian version of the SANS instrument is valid and reliable for measuring negative symptoms in people with schizophrenia in Indonesia.